Cash flow forecasting - Fight, Andrew (Essential capital markets., 2006)
Budgets are like road maps -- they provide a direction for a corporates financial management. Balance sheets and statements of revenues also provide insights into how well a company is following that direction. But cash flow and cash flow forecasts are what guide the day-to-day itinerary for an organization. Budgets and cash flow are dynamic -- adjustments and changes can and should occur. If you understand what you are looking at, you can use cash flow to create better budgets and thus more accurate cash flow forecasting. Cash Flow Forecasting outlines the techniques required to undertake a detailed analysis of the cash flow dynamics of the business from both a historical and forward looking perspective. Cash Flow Forecasting explains how to: * Determine appropriate cash flow figures from pro forma financial statements * Interpret detailed cash flow forecasts and understand the difference between profit and cash flow * Conserve or generate cash in the short term * Evaluate different methods of project evaluation * Recognize the limitations of accounting information in valuing companies *Inspired by basic entry level training courses that have been developed by major international banks worldwide * Will enable students and those already in the finance profession to gain an understanding of the basic information and principles of cash flow forecasting * Includes questions with answers, study topics, practical "real world" examples and extensive bibliography